2015
DOI: 10.1080/10538712.2015.1022293
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on Childhood Sexual Abuse, Diurnal Cortisol Secretion, and Weight Loss in Bariatric Surgery Patients

Abstract: Childhood sexual abuse increases risk for adult obesity. A potential contributing factor is altered cortisol secretion. In this pilot study, relationships among childhood sexual abuse, diurnal salivary cortisol secretion, and weight loss were explored in 17 bariatric surgery patients. Measurement points were before surgery (baseline) and 3 and 6 months after surgery. Childhood sexual abuse was measured by the Childhood Trauma Questionnaire. The results showed moderate but nonsignificant positive correlations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…However, the two groups did not differ in weight loss or waist circumference (117). By contrast, Hulme et al found that BS did not affect daily cortisol secretion patterns during the first 6 months after surgery, although morning cortisol showed a slightly non-significant post-operative increase (122).…”
Section: Non-metabolic Bs-induced Endocrine Alterationsmentioning
confidence: 88%
“…However, the two groups did not differ in weight loss or waist circumference (117). By contrast, Hulme et al found that BS did not affect daily cortisol secretion patterns during the first 6 months after surgery, although morning cortisol showed a slightly non-significant post-operative increase (122).…”
Section: Non-metabolic Bs-induced Endocrine Alterationsmentioning
confidence: 88%
“…Finally, a pilot study suggests that altered cortisol secretion in individuals who suffered from CSA is a contributing factor to the risk of adult obesity ( Hulme et al, 2015 ). Elevated glucocorticoid hormones in the CSA population might favor excess eating behaviors and negatively affect weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Exploration of the potential impact of childhood trauma on post-operative outcomes, including long-term weight outcome, may also be useful for informing the necessity and timing of interventions.Prior literature on the impact of a history of childhood trauma on subsequent weight loss has been limited and the results mixed. Although one pilot study found that childhood sexual abuse was associated with greater weight loss (29), other research found no association between adverse childhood experiences as post-surgery weightloss (30), and yet other investigations suggest poorer weight losses (31,32). Prospective studies are needed to examine the effects of childhood trauma and interventions to help bariatric surgery patients with a history of abuse and neglect achieve optimal health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%